PENGGUNAAN MEDIA KARTU KATA BERGAMBAR UNTUK MENINGKATKAN KETERAMPILAN MENULIS SISWA KELAS IV SD NEGERI 1001 BATANG BULU - Pangaduan Siregar; Lailan Aprina Siregar, Nurhalimah Harahap (JOURNAL OF COMMUNITY DEDICATION, 2023)
The aim of this research is to find out how to use picture word card media to improve students' writing skills in class IV animal and plant material at SD Negeri 1001 Batang Bulu. The research used is classroom action research. Based on the research results, it can be concluded that in the pre-cycle students' writing was still considered not good, students did not understand the proper and correct use of punctuation when writing. In cycle I, writing skills were categorized as still not good because there were still students who wrote spacingly and did not put punctuation marks such as periods, commas, questions, exclamations and dashes. Students have begun to be able to hold writing instruments correctly but are not yet perfect as taught. In cycle I there were still students who wrote without spacing, and did not use punctuation such as periods, commas, questions, exclamations and dashes. Then in cycle II students' writing skills can be categorized as good. Students are able to hold writing instruments correctly, students' creativity in using language styles and forms begins to be structured and the neatness of their writing and cleanliness improve quite well in cycle II.